SOIi^E OBSERVATIONS ON THE CARP FRY RESOURCES OF THE RIVER GODAVARI NEAR RAJAHMUNDRY, ANDHRA PRADESH - Ibrahim, K H (Indian Journal of Fisheries, 2011)
AVAILABLE information on the fish seed resources, particularly of peninsularrivers and the quality and quantity of fish spawn collected therefrom, is ratherfragmentary. Chacko (1946) mentions about the spawning of the majorcarps Catla catla, Labeo fimbriatus, Labeo calbasu and Cirrhina cirrhosa in theGodavari and the Krishna from July to September. According to him Catlapredominates (60%) in the fry and fingerlings collected from the canals andpaddy fields; while in the river collections, fry of L. fimbriatus (60%) predominate.AUkunhi (1947) recorded the natural occurrence of Cirrhinamrigala in the Godavari and found the species forming about 20% of thetotal fish landings at Rajahmundry. Alikunhi et al. (1949) collected eggsand hatchUngs of L., calbasu in large numbers from the Godavari below theanicut at Bobberlanka, on 22-7-1948